Andrew Jackson and the miracle of New Orleans [large type] : the battle that shaped America's destiny - Kilmeade, Brian; Yaeger, Don (Random House Large Print, 2017)
A portrait of the seventh American president focuses on his formative military prowess during the War of 1812 and his pivotal contributions to the capturing of New Orleans from the British.